Listening skills and Vocabulary acquisition among 10th-grade English as a Foreign Language Learners, school year 2025-2026 - Cango Patiño, Adriana Elizabeth; Thalía Valeria Ocampo Arévalo , Thalía Valeria Ocampo Arévalo; Muñoz Alvarez, Angélica Natalí; Lojan Caicedo, Jocelyn Andrea (Ciencia y Reflexión, 2026)
In English as a Foreign Language (EFL) contexts, listening comprehension and vocabulary knowledge are closely connected skills that support learners’ access to meaningful input. This study examined the relationship between listening skills and vocabulary acquisition among tenth-grade EFL learners at a private fiscomisional institution in Loja, Ecuador. A quantitative, cross-sectional correlational design was applied with a sample of 20 students. Data were collected through two CEFR-aligned achievement tests at the A2+ level, selected to match the national curriculum standards for this grade. Listening performance was evaluated through four subskills: understanding the speaker’s purpose, making inferences from context, processing connected speech, and recognizing specific information. Vocabulary knowledge was assessed across the dimensions of form, meaning, and use. The results revealed moderate performance in both variables, defined as scores falling within the 60-75% range of the predetermined assessment scale, with greater difficulty observed in inferential listening and semantic depth. A Pearson correlation analysis showed a statistically significant positive relationship between listening skills and vocabulary acquisition(r=.612,p<.01), indicating that students with stronger vocabulary knowledge tended to demonstrate higher listening comprehension. These findings highlight the importance of integrating vocabulary development within listening instruction to enhance overall communicative competence